Research and Design of an X-Band UHF Power Amplifier - Nguyen Xuan Luong; Thanh Thuy Thi Dang; Nguyen Phung Bao; Nguyen Van Bac (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. A method for designing power amplifiers for use in the transmitting channels of X-band transceiver modules is investigated. The design process was aimed at optimizing the relationship between the basic amplifier characteristics, including the operating frequency band, output power level, output linearity, high harmonics suppression, etc.  Aim. Investigation of a method for designing an X-band UHF power amplifier, which is capable of optimizing the relationship between its main characteristics.  Materials and methods. Theoretical calculations were combined with experimental studies into the design of a UHF power amplifier. The stages of the design process are described in detail, including major ideas, principal circuits, and strip circuits. Evaluations were conducted using the Keysight ADS high frequency circuit simulation tool.  Results. A method for designing X-band UHF power amplifiers on the basis of a close combination of theory, simulation, and experimental adjustment was described in detail.  Conclusion. A prototype of an X-band PA was developed; an approach to developing a methodology for manufacturing, measuring, and testing X-band PAs is described.